2005
DOI: 10.1590/s0370-44672005000300009
|View full text |Cite
|
Sign up to set email alerts
|

Lixiviação da calcopirita com cloreto férrico e cloreto de sódio

Abstract: RESUMO: Objetivou-se avaliar o material lixiviado em solo cultivado com noni (Morinda Citrifolia L.) irrigado com águas salinas, no sentido de verificar os teores de sódio e cloreto aos 60, 90 e 110 dias após o transplante das mudas de noni (DAT) sob delineamento estatístico em blocos ao acaso 5 x 2 x 2, sendo cinco níveis salinos da água para irrigação (0,3; 1,5; 3,0; 4,5 e 6,0 dS m-1) em dois ambientes (telado-T e campo aberto-CA com ausência-AMO e presença de matéria orgânica no solo-PMO) com cinco repetiçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
2
1
0
1
Order By: Relevance
“…Much better extractions are observed for higher NaCl concentrations as copper dissolution reaches a maximum slightly above 90%, at 1.0-2.0 mol/L NaCl. These results confirm the positive effect of the presence of chloride ions on chalcopyrite leaching (Carneiro and Leão, 2005;Hirato et al, 1986;Majima et al, 1985;Skorobian et al, 2005). Under similar conditions to those of the present work, Carneiro and Leão (2005) have shown that the presence of sodium chloride also increased chalcopyrite leaching with ferric chloride.…”
Section: Influence Of Sodium Chloride Concentration On Chemical Leachingsupporting
confidence: 92%
See 2 more Smart Citations
“…Much better extractions are observed for higher NaCl concentrations as copper dissolution reaches a maximum slightly above 90%, at 1.0-2.0 mol/L NaCl. These results confirm the positive effect of the presence of chloride ions on chalcopyrite leaching (Carneiro and Leão, 2005;Hirato et al, 1986;Majima et al, 1985;Skorobian et al, 2005). Under similar conditions to those of the present work, Carneiro and Leão (2005) have shown that the presence of sodium chloride also increased chalcopyrite leaching with ferric chloride.…”
Section: Influence Of Sodium Chloride Concentration On Chemical Leachingsupporting
confidence: 92%
“…These results confirm the positive effect of the presence of chloride ions on chalcopyrite leaching (Carneiro and Leão, 2005;Hirato et al, 1986;Majima et al, 1985;Skorobian et al, 2005). Under similar conditions to those of the present work, Carneiro and Leão (2005) have shown that the presence of sodium chloride also increased chalcopyrite leaching with ferric chloride. However, the effect was less pronounced: copper extraction increased from 70% (without NaCl) to 81% (1 mol/L NaCl).…”
Section: Influence Of Sodium Chloride Concentration On Chemical Leachingsupporting
confidence: 92%
See 1 more Smart Citation
“…Sabe-se que a reação de oxidação da calcopirita utilizando íons férricos possui uma cinética lenta e sua taxa de oxidação diminui com o tempo. Isso é atribuído à formação de uma camada de passivação durante a lixiviação em condições oxidantes, o que inibe a reação [13].…”
Section: (20%)unclassified